FEATURES OF DEVELOPING A 2D AUTHORIZED GAME USING THE UNREAL ENGINE 5 - KRYLIK, LYUDMILA; YERMOLAIEVA, MILENA (Herald of Khmelnytskyi National University. Technical sciences, 2025)
The work presents the features of developing an author's 2D game using Unreal Engine 5. The method of work is to improve the gameplay of a 2D game by expanding the functionality of the Unreal Engine 5 game engine. Unreal Engine 5 is a modern game engine for game development, which has tools for creating exciting spatial worlds, animations and game mechanisms. This engine is limited in the development of 2D games, but other additional tools to facilitate and improve the development work. The built-in Paper2D plugin and the free PaperZD plugin have greatly facilitated and accelerated the development of a 2D game, as well as setting up multi-directional animations, creating a state machine, creating AnimationInstance, AnimationSource Blueprints. In addition, Unreal Engine required certain settings that are needed not only to improve the quality of graphics, but also to avoid graphic artifacts and improve the game. During development, a problem was discovered with the settings of collisions for interaction and the character anchor. The research found a solution to this problem and implemented it in a 2D game. Taking into account all the features of working with 2D games, in the Unreal Engine 5 game engine, it is possible to develop a game with improved gameplay, high-quality graphics in a shorter period of time. Comparing the development of the author's 2D game with another 2D project developed in Unreal Engine 5 without using the described technique and the PaperZD plugin, it was found that using the PaperZD plugin and using files with the json extension significantly accelerated and improved the development of the 2D game. Changing the project settings and using a modified PostProcessing Volume significantly improved the graphics and performance of the game. The developed author's 2D game successfully passed testing and has improved gameplay, high-quality graphics and proper performance.
Keywords: 2D games; Unreal Engine 5; gamedev; indie development